2020
DOI: 10.1113/ep088764
|View full text |Cite
|
Sign up to set email alerts
|

Tissue oxygenation in peripheral muscles and functional capacity in cystic fibrosis: a cross‐sectional study

Abstract: New Findings What is the central question of this study?How do peripheral muscle tissue oxygenation and physical conditioning levels of children and adolescents with cystic fibrosis compare to demographically matched controls? What is the main finding and its importance?Children and adolescents with cystic fibrosis consumed more oxygen, more quickly and exhibited slower recovery, demonstrating that there may have been deficiencies in oxygen supply related to both oxygen uptake and oxygen transport. Abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
2
1
Order By: Relevance
“…However, we did find that tissue oxygenation in the quadriceps was lower in the masked versus sham condition for the submaximal "shifts" in males and the maximal "shift" in females. While these decreases in muscle tissue oxygenation were statistically lower in the masked vs. sham condition, the absolute difference between masked and unmasked conditions was quite small (0.4-2.8%) and within the range observed in previous research in adults during masked and unmasked exercise [15], as well as in research involving children of a similar age during exercise without wearing masks [27]. Thus, any differences are likely to have minimal clinical importance.…”
Section: Discussionsupporting
confidence: 65%
“…However, we did find that tissue oxygenation in the quadriceps was lower in the masked versus sham condition for the submaximal "shifts" in males and the maximal "shift" in females. While these decreases in muscle tissue oxygenation were statistically lower in the masked vs. sham condition, the absolute difference between masked and unmasked conditions was quite small (0.4-2.8%) and within the range observed in previous research in adults during masked and unmasked exercise [15], as well as in research involving children of a similar age during exercise without wearing masks [27]. Thus, any differences are likely to have minimal clinical importance.…”
Section: Discussionsupporting
confidence: 65%
“…Of the investigations that used the MSWT in children with CF (Coelho et al., 2007, 2020; Cox et al., 2006; del Corral et al., 2020; Pérez et al., 2014; Urquhart et al., 2012; Vendrusculo et al., 2019; Vendrusculo et al., 2020), the present study had the lowest average age and smallest age range, thus confirming the sample as exclusively pediatric. Research by Vendrusculo et al.…”
Section: Discussionsupporting
confidence: 74%
“…Of the investigations that used the MSWT in children with CF (Coelho et al, 2007(Coelho et al, , 2020Cox et al, 2006;del Corral et al, 2020;Pérez et al, 2014;Urquhart et al, 2012;Vendrusculo et al, 2019;Vendrusculo et al, 2020), the present study had the lowest average It is important to note that, although our results showed no relationship between distance walked and age, some of the younger participants had difficulty understanding the MSWT and showed a lack of motivation to perform the test. This behavior may have compromised the actual exercise capacity of some children, since studies have shown that performance in this population depends on motivation and age (Bento et al, 2017).…”
Section: Discussioncontrasting
confidence: 53%
“…PCD patients have reduced peak oxygen consumption due to decreased PF and PAL [ 6 ]. Peripheral muscle tissue oxygenation is associated with functional capacity in CLD [ 25 ]. Our results showed a 46.6 m and 48.12 m increase in the 6MWD and ISWD, respectively, with AVGs.…”
Section: Discussionmentioning
confidence: 99%